Respuesta del cultivo de rosas (Rosa sp), a la aplicación de cuatro niveles de relación nitrógeno-potasio como fertilización complementaria, en la zona de Cayambe, Provincia de Pichincha - Mera Vásquez, Carlos Vinicio (2011)
This research evaluated the "Response of crop cultivation of roses (Rosa sp.) Implementing four nitrogen fertilization levels/potassium as complementary fertilization in the area of Cayambe, Pichincha Province." We use da completely randomized design, DCA, statistical analysis of variables test was performed by Duncan's multiple range at 5% probability. The number of plants used in the investigation was7140, with 15 experimental and 10 plants per experimental unit chosen at random. We used four doses of fertilizer ammonium nitrate (NO3-NH4 +) and potassium nitrate (NO3-K) whose applications were made by weekly doses in the supplemental fertilization treatment 1 + ratio nitrogen /potassium (1.0N/0.9K), supplemental fertilization treatment 2 + ratio nitrogen/ potassium (1.20N/1.0K), additional fertilization treatment 3 + ratio nitrogen/ potassium (1.4N/1.0K), additional fertilization treatment 4 + ratio nitrogen/ potassium (1.2KN/1.4)........